2021
DOI: 10.1038/s41372-021-01228-x
|View full text |Cite
|
Sign up to set email alerts
|

Worsened short-term clinical outcomes in a cohort of patients with iNO-unresponsive PPHN: a case for improving iNO responsiveness

Abstract: To identify distinguishing characteristics of neonates with persistent pulmonary hypertension of the newborn (PPHN) unresponsive to inhaled nitric oxide (iNO) and evaluate the use of milrinone in this cohort. STUDY DESIGN: Retrospective chart review of 99 neonates with PPHN treated with iNO over a five-year period at a quaternary neonatal intensive care unit. RESULTS: Neonates with iNO-unresponsive PPHN had an increased number of ventilator days (10 vs 7 days, p = 0.02), greater length of hospital stay (30 vs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…23 Dillard et al reported that infants who were nonrespondent to iNO and received adjuvant milrinone had a better prognosis, better oxygenation, and fewer hemodynamic changes. 28 Nevertheless, in some cases, the addition of milrinone to iNO had no significant effects on the improvement of treatment. 29 Overall, injectable milrinone, which showed satisfactory outcomes in the present study, can be used as an adjuvant or alternative therapy to PPHN management, especially in centers with limited access to iNO.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…23 Dillard et al reported that infants who were nonrespondent to iNO and received adjuvant milrinone had a better prognosis, better oxygenation, and fewer hemodynamic changes. 28 Nevertheless, in some cases, the addition of milrinone to iNO had no significant effects on the improvement of treatment. 29 Overall, injectable milrinone, which showed satisfactory outcomes in the present study, can be used as an adjuvant or alternative therapy to PPHN management, especially in centers with limited access to iNO.…”
Section: Resultsmentioning
confidence: 98%
“…According to previous research, injectable milrinone may improve the prognosis of infants with iNO-resistant PPHN. 23,28 Mat Bah et al…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…El-Ghandour et al (29) showed that the combination of oral sildena l and intravenous milrinone did not increase the side effects and was more effective than monotherapy with any of the drugs. Also, previous studies have shown that injectable milrinone may improve prognosis in infants with iNO-resistant PPHN (24,30) . Mat Bah et al reported a worse prognosis among iNO-resistant PPHN neonates, especially in the idiopathic type (24) .…”
Section: Discussionmentioning
confidence: 97%
“…Mat Bah et al reported a worse prognosis among iNO-resistant PPHN neonates, especially in the idiopathic type (24) . Also, Dillard et al reported that infants who were non-respondent to iNO and received adjuvant milrinone had a better prognosis, better oxygenation, and less hemodynamic change (30) . However, in some cases, the addition of milrinone to iNO has shown no signi cant effect in improving treatment (31) .…”
Section: Discussionmentioning
confidence: 99%